Effect of Grain refining Additives on Microstructure and Mechanical Properties of the Commercial Available Magnesium alloys AZ31 and AM50. (2015) - Neh, K.; Ullmann, M.; Kawalla, R.
Abstract: In order to fulfill the requirements of lightweight design, the establishment of magnesium wrought alloys is an important issue. To achieve this aim the development of new alloy compositions is essential. Therefore, the influence of different additives to commercial available magnesium alloys (AZ31, AM50) on microstructure and mechanical properties is investigated in this work. After casting of the magnesium alloys into a plate-shaped mold, hot rolling in laboratory scale to produce sheets with a final thickness of 2 mm was conducted. Mechanical properties and microstructure of the finish rolled sheets were characterized. The investigations of this work show, that casting and subsequent hot rolling enables the production of magnesium alloy sheets containing grain refining additives. Sufficient mechanical properties of these sheets are achievable using 0.3 wt% AlN or Tiboral for AM50 and 0.25wt % SiC for AZ31.